Spatial plots : virtuality and the embodied mind in Baricco, Camilleri and Calvino - Beltrami, Marzia (Legenda, 2021)
In discussions about plot, causality and chronology are sometimes held out as the only possible organising principles. And yet readers often transmute fragmented writings, parallel storylines, or tales within tales into a meaningful whole. Other patterns play a role in guiding their attention and, as Beltrami suggests, they invite us to make sense of narratives as spaces to be explored. The critical analysis of selected works by Alessandro Baricco (b. 1958), Andrea Camilleri (1925-2019) and Italo Calvino (1923-1985) dovetails broader theoretical reflection about th eways in which narrative comprehension, far from being 'extraordinary, ' is a practice embedded in our everyday life and deeply rooted in the sense-making strategies we use to negotiate the world around us. Drawing on recent studies in cognitive literary criticism and cognitive narratology, this book investigates the techniques that elicit such 'spatial' understanding and illustrates how a cognitive-oriented approach may help illuminate the internal workings of certain narrative texts and open up novel readings. The images of map, trajectory and fractal are offered to represent three types of spatial plots, three ways in which stories may be understood and navigated as spaces.